Composition of herring and cod fillets from the North and the Baltic Sea – Detecting added water. (January 2020) - Bisenius, S.; Neuhaus, H.; Effkemann, S.; Heemken, O.; Bartelt, E.; Lang, T.; Haunhorst, E.; Kehrenberg, C.
Abstract: For the labelling of added water in fish fillets and other unprocessed fishery products in accordance with Regulation (EC) No. 1169/2011, it is essential to know the natural species-specific water content of the fish meat. This knowledge serves as a basis for the detection of undeclared water addition to fish products in order to prevent food fraud. As there are few studies focusing on the reference values of fish meat with guaranteed unchanged water and protein content, this study was carried out to obtain reference values for the detection of added water in herring and cod fillets. This study presents for the first time reference values determined by standardized methods of untreated cod (n = 30) and herring (n = 48) fillets from two fishing areas within the Baltic Sea FAO fishing area 27 IIIc (22) and the North Sea FAO 27 subarea IVb. This includes the different influences of species, habitat and season on water, protein and fat content. The average water content of herring fillets from FAO Area 27 IIIc (22) in December was 77.0% and 70.9%, respectively. This great difference demonstrates that it is difficult to establish a uniform value for the water, protein or fat content of herring fillets. In contrast, cod fillets from the Baltic Sea with an average water content of 79.7% and 79.5%, respectively, showed only a moderate difference. In addition, this study demonstrates that the water/protein ratio appears to be a good tool for detecting added water in fish products, especially for herring fillets as a fatty fish species. Highlights: Reference values e.g. for water, protein and fat content of herring and cod fillets. Naturally occurring carbonate and monophosphate contents in untreated fish fillets. Demonstration of the influence of catch area and date on flesh composition. Significant differences in the composition of the fillets within a FAO area. Results facilitate assessment of added water and food additives in fish fillets.